Tree Strata Structure in an Ecotone among the Amazon Forest Types: A Comparative Study. Issue 6 (8th July 2019) - Canetti, Aline; Braz, Evaldo Muñoz; de Mattos, Patrícia Póvoa; Figueiredo Filho, Afonso; Basso, Renato Olivir
Abstract: This work aimed to describe the structural dynamics of the Transitional Amazonian Forest and to evaluate whether the most abundant tree species present a structural pattern. As it is an ecotone composed of two forest types, a high composition complexity is expected. Forest analysis occurred with six 100 percent inventories data considering all trees with diameter at breast height ≥15.7 in., totalizing over 13 000 ac. The study areas were compared in terms of tree density, number of species, and importance value of the most abundant species. The Morisita index and the cluster analysis tested the forests similarity. We also evaluated the importance value of species in the upper and middle strata. Differences between study areas were detected regarding tree density and number of species. However, the forests presented more than 75 percent similarity and were grouped in three structural clusters. Some species showed alternations of dominance in the middle and upper strata. Although the forest is an ecotone, the trees had a structural pattern, where the same species dominate large areas, allowing us to apply the results on a huge scale.